Factors Associated with Pre-hospital Delay before Reperfusion Therapy in Patients with ST-Segment Elevation Myocardial Infarction - Kafle, Ram Chandra; Paudel, Navaraj; Jha, Girija Shankar; Sharma, Dibya; Alurkar, Vijay Madhav (Journal of Lumbini Medical College, 2018)
Introduction: Cardiovascular disease remains the main cause of death in the world, and myocardial infarction represents the main contributor to this mortality. Timely restoration of myocardial blood flow with reperfusion therapy is crucial. Pre-hospital delay is a major obstacle for early reperfusion therapy and has negative impact on mortality and left ventricle function. Methods: A prospective study was carried in cardiology unit of a medical college from August 2013 to December 2017. Cases of acute ST segment elevation myocardial infarction that have undergone thrombolysis were recruited. Results: Out of 450 patients with ST Elevation Myocardial Infection (STEMI), delayed presentation was seen in 288 (64%) for >6 hrs and 108 (24%) patients for >12 hrs. The duration from onset of symptoms to the presentation in the emergency room (pre-hospital delay) was 12.66 hrs (SD=14.19, range = 30 min to 72 hrs). The door to needle time was 54 min (SD=24) The major factors for pre-hospital delay were misinterpretation of symptoms (59%) and transportation problems (31%). Conclusion: Misinterpretation of symptoms remain the most common cause of delayed presentation. Health education for public awareness can reduce the delay. Extension of thrombolytic therapy to district hospital and primary health center level after basic training for medical officer with checklist and collaboration in form of telemedicine with referral cardiac center may have major impact on morbidity and mortality reduction in acute STEMI patients with early reperfusion therapy. DOI: https://doi.org/10.22502/jlmc.v6i2.228